Handbook of sociology of aging - Settersten, Richard A.; Angel, Jacqueline L. (Handbooks of Sociology and Social Research, 2011)
The Handbook of Sociology of Aging is the most comprehensive and engaging treatment of the field over the past 30 years. It is an indispensable resource for scholars, policy makers, and aging professionals alike. The Handbook of Sociology of Aging contains 45 far-reaching chapters, authored by nearly 80 of the most renowned experts, on the most pressing topics related to aging today. With its recurring attention to the social forces that shape human aging, and their social consequences and policy implications of it, the contents will be of interest to everyone who cares about what aging means for individuals, families, and societies. Two forwards highlight the significance of the handbook for scholarship and and policy-making on aging. The chapters illustrate the field?s extraordinary breadth and depth, which have never before been represented in a single volume. They range from foundational matters, including classic and contemporary theories and methods, to topics of longstanding and emergent interest, such as social diversity and inequalities, social relationships, social institutions, economies and governments, social vulnerabilities, public health, and care arrangements. The volume closes with a set of personal essays by senior scholars who share their experiences and hopes for the field, and an essay by the editors that previews some of the most exciting aspects for the decade ahead. The Handbook of Sociology of Aging showcases the very best that sociology has to offer the study of human aging.